Traffic of Endogenous, Transduced, and Endocytosed Prolactin in Rabbit Lacrimal Acinar Cells - Wang, Yanru (2007)
The rabbit lacrimal gland undergoes an immunophysiological transformation during pregnancy, reminiscent of that of the mammary gland as it prepares to deliver secretory IgA into the nascent fluid product. The contents of TGF-β and prolactin (PRL) within ductal epithelial cells increase, and their primary localizations shift from the apical- to the basal cytoplasm, suggesting a transformation from exocrine- to paracrine secretion. Studies with ex vivo acinar cell models demonstrated that elevated PRL suppresses traffic of secretory proteins into the regulated exocrine apparatus and directs them into a novel, induced, regulated paracrine apparatus (Wang et al., Am. J. Physiol. 292, E1122-E1134, 2007). However, it was not clear whether PRL itself entered the induced paracrine apparatus. In the present study, confocal immunofluorescence microscopy revealed that natively-expressed PRL and over-expressed PRL co-localized with PRL receptors (PRLR); rab11, a marker for the recycling endosome; γ-adaptin, a marker for the Golgi complex and trans-Golgi network; and rab7, a marker for the autophagic - lysosomal apparatus. Natively expressed, over-expressed, and endocytosed PRL also co-localized with rab4 and rab5A, markers for the early endosome, and with rab3D, a marker for regulated exocrine secretory vesicles. Endocytosed PRL was stored in intact form and released in response to stimulation with carbachol. Subcellular fractionation analysis detected relative excesses of PRL over PRLR in fractions that contained fragments of the recycling endosome and fractions that contained both secretory vesicle fragments and pre-lysosomal- and autolysosomal fragments. EM-gold microscopy demonstrated PRL within small vesicles, consistent with endosomes or secondary lysosomes, and in large vesicles, consistent with regulated secretory vesicles. The secretory vesicles were preponderantly localized in the apical cytoplasm of control cells, and in the basal cytoplasm of PRL-over-expressing cells. These results indicate that when lacrimal epithelial cells synthesize PRL, and when they endocytose it from their ambient medium, they traffic it both into the endosomes that constitute the constitutive transcytotic - paracrine apparatus and also into regulated secretory vesicles, which are associated with the exocrine apparatus at low PRL levels and with the induced paracrine apparatus at high PRL levels.